Design Of A Decision Support System For The Provision Of Assistance To Small Medium Industry (Smi) At The Industrial And Trade Service Of Bengkulu Province Using The Topsis Method - Agung Kharisma Hidayah; Dwita Deslianti; Marhalim Marhalim; Yozi Anggara (Jurnal Komputer, Informasi dan Teknologi, 2023)
The Department of Industry and Trade (DISPERINDAG) of Bengkulu Province has the function of preparing regional government program planning for Bengkulu Province, one of these programs is providing assistance to small and medium industries in Bengkulu Province. The problem of this research is the selection process for determining the recipient of the assistance. This selection process is still done manually by selecting one by one each IKM document that will receive assistance, this is certainly quite prone to errors. This manual process results in the length of the selection process being carried out. The results of selection decisions are sometimes vulnerable to non-objectivity from the Bengkulu Province DIPERINDAG because there is no mathematical determination because all decisions come from humans. The results of this study have created a Decision Support System (DSS) to simplify the data processing process and shorten the completion time while improving the quality of decisions in determining the priority of beneficiaries to get maximum results, the TOPSIS method has also been applied. In this method, a calculation has been carried out on the IKM which is a candidate for assistance based on predetermined criteria.